THE INFLUENCE OF INCENTIVES AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT UP CREATIVE SPACE & COFFEE MANADO - Euriene Theodora Marzioz Luwuk; David P. E. Saerang; Emilia M. Gunawan (Cahaya Ilmu Bangsa, 2025)
This research aims to analyze the influence of incentives and work discipline on employee performance at UP Creative Space & Coffee Manado. The main objective of this research is to analyze the influence of incentives on employee performance, the influence of work discipline on employee performance, and the combined influence of incentives and work discipline on employee performance. The sample of this research was all 33 employees of UP Creative Space & Coffee Manado, using saturation sampling for the sampling technique. The results shows that incentives and work discipline partially have a positive but not significant effect on individual employee performance at UP Creative Space & Coffee Manado. However, simultaneously, these two variables have a positive and significant effect on employee performance. In this study, incentives and work discipline at UP Creative Space & Coffee Manado were found to positively and significantly influence employee performance when applied simultaneously, highlighting their importance in improving overall organizational outcomes.